2011
DOI: 10.1007/s10705-011-9425-5
|View full text |Cite
|
Sign up to set email alerts
|

GIS-model based estimation of nitrogen leaching from croplands of China

Abstract: Nitrogen (N) is the most widely used fertilizer nutrient, and its application has increased substantially in recent decades in China. N loss through leaching has been recognized as one of the most common agricultural sources of groundwater contamination. Thus, prediction of N leaching from cropland is crucial for preventing groundwater pollution. This paper quantifies nitrogen leaching from China's croplands, identifies its spatial distribution under current cropping systems at national scale, and finally puts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…This suggested that the decrease of sediment yield owing to change of hydrologic processes contributed to the decrease of organic N and P yields due to the future land use change (Annex, Tables A-5 and A-6). It is known that hydrologic processes also influence inorganic N leaching from soil to groundwater and river water (Qiu et al, 2011). Our results indicated that groundwater for 2036 land use was less than that for 2006 land use in each climate condition.…”
Section: Impact Of Land-use On Water Qualitymentioning
confidence: 62%
“…This suggested that the decrease of sediment yield owing to change of hydrologic processes contributed to the decrease of organic N and P yields due to the future land use change (Annex, Tables A-5 and A-6). It is known that hydrologic processes also influence inorganic N leaching from soil to groundwater and river water (Qiu et al, 2011). Our results indicated that groundwater for 2036 land use was less than that for 2006 land use in each climate condition.…”
Section: Impact Of Land-use On Water Qualitymentioning
confidence: 62%
“…To quantify N loading at national scale, we applied China-DNDC for all croplands in China. Qiu et al (2011) implemented national-scale simulations by linking China-DNDC to the Chinese agricultural database. Results from the simulations indicated that (1) the total amount of N leached from all Chinese croplands was about 4.6 million t N/year (or 48 kg N/ha) for the simulated year (1998); and (2) the N leaching rates highly varied across the country, ranging from 12 kg N/ha to 216 kg N/ha, driven by the interacting effects of climate, soil and management conditions.…”
Section: Nitrogen Leachingmentioning
confidence: 99%
“…Field experiments play an important role in monitoring crop yields and nitrate leaching as a basis to evaluate the effects of different management measures (Perego et al, 2013;Zhang et al, 1996), but they are often time-and labor-consuming and the results are difficult to scale up spatially or temporally. Prediction of yield or nitrate leaching at a larger scale has to rely on some successful mathematical formulas (Qiu et al, 2011). Some models based on hydrology are commonly used to predict nutrient loadings in watershed scale, such as SWAT (Wang et al, 2014a) and MIKE SHE (Vansteenkiste et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A large number of researches have used the DNDC model to identify best management practices for higher crop yield or lower pollution risk (Gopalakrishnan et al, 2012;Werner et al, 2012). Integrating detailed N transformation with hydrological processes, the model was also regarded to be able to simulate nitrate leaching (Qiu et al, 2011), however, the applicability of the model in this regard has been rarely tested (Li et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%